(3GdOhdI h GdJfejI aj GdhWf GdYQHj (B:s (3eMGhdI dGSJHGb GdJZjjQ GdYGdej aj Xd efgLjI GdJMdjd GdeSJbHdj (B/s - (3GdRHjOj, MSf dWja cGXes ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2008)
(3GdbVGjG GdYGeI aj eaghe GdOhdI h OhQgG , eaghe GdOhdI aj GdhWf GdYQHj (B: (3GdeVGejf h GdGTcGdjGJ , GTcGdjI GdJfejI HhGSWI GdOhdI aj GdhWf GdYQHj , GSJHGb GdJZjjQ GdYGdej (B: (3GdebGQHI GdeSJbHdjI ddOhdI aj GdhWf GdYQHj , eMOOGJ eSJbHd GdOhdI GdbWQjI h CNjQG GdHOGFd GdeSJbHdjI dgPg GdOhdIs
(3eQGLY U(B.511s
Keywords: (3GdHdOGf GdYQHjI ` GdJfejIs; (3GdJfejIs; (3GdJfejI ` GdHdOGf GdYQHjIs